Histopathological evaluation of endometrial patterns in workup of abnormal uterine bleeding - Raman, Jayasree; Pushpangadan, Prakash; Philip, Febby K.; Pillai, Shobha S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Abnormal uterine bleeding (AUB) is defined as bleeding pattern that differs in frequency, duration and amount from the normal cyclical flow. Endometrium in AUB vary depending on etiology and age. The present study attempts to categorize the histopathology of endometrium in abnormal uterine bleeding in women of various age groups. Methods: A hospital based prospective study was carried out in 220 cases of abnormal uterine bleeding. Paraffin processed endometrial biopsies analyzed correlating the clinico-radiological data. Endometrial samples of infertility and pregnancy related bleeding were excluded. Results: 220 cases of AUB from 25 years to 78 years of age were evaluated under three groups, reproductive (23%), perimenopausal (52%) and postmenopausal (25%). AUB was most common in the perimenopausal group. The predominant pattern seen was physiological cyclical endometrium (67.2%). Disordered proliferative endometrium (18.63%) was the predominant abnormal pattern. Malignant lesions were (99.5%) in postmenopausal age and disordered proliferative endometrium seen predominantly (65.85%) in perimenopausal age group. As per PALM-COEIN classification, uterine structural abnormalities (PALM) were found in 70 (31.9%), non-structural causes (COEIN) in 150 (68.1%). Endometrial thickness >16 mm on radiology were seen in endometrial carcinoma. Conclusions: Endometrial morphology vary with ovulatory abnormalities, anovulation and uterine abnormalities. Acronym PALM-COEIN is useful in categorizing AUB. The incidence of disordered proliferation, hyperplasia and malignancy seen in extremes of age, reiterates that early clinic-radiological workup and endometrial study are the mainstay in early detection of lesions.